2016
DOI: 10.1080/10749039.2016.1194433
|View full text |Cite
|
Sign up to set email alerts
|

Field Ecology: A Modest, but Imaginable, Contestation of Neoliberal Science Education

Abstract: Abstract:Science education has become a valuable market tool, serving the knowledge economy and technocratic workforce that celebrates individualism, meritocracy, entrepreneurship, rational thought, and abstract knowledge. Field ecology, however, could be a modest, but imaginable contestation of market-driven neoliberal ideology. We explored diverse high school youths' meaning making of a summer field ecology research experience. Youths' narratives, elicited with a modified card sort and qualitative interviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In their traditional in‐person formats, field courses are an important tool for retention, success, and equity in science majors, especially for underrepresented minorities (URM) (Beltran et al., 2020). These benefits emerge from the many positive factors impacted by field courses including self‐efficacy (Beltran et al., 2020; Dillon, 2013; Kortz et al., 2020), science and peer community (Epstein et al., 2015; Anderson and Miskimins, 2006; Haywood et al., 2016; Madden et al., 2012), and comfort in the outdoors (Carlone et al., 2016; van der Hoeven Kraft et al., 2011; Jolley et al., 2018). Despite these benefits, university support for field courses is diminishing, highlighting the importance of research that explores barriers, outcomes, and impacts of field courses (Cotton & Cotton, 2009; Moore, 2001; Smith, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their traditional in‐person formats, field courses are an important tool for retention, success, and equity in science majors, especially for underrepresented minorities (URM) (Beltran et al., 2020). These benefits emerge from the many positive factors impacted by field courses including self‐efficacy (Beltran et al., 2020; Dillon, 2013; Kortz et al., 2020), science and peer community (Epstein et al., 2015; Anderson and Miskimins, 2006; Haywood et al., 2016; Madden et al., 2012), and comfort in the outdoors (Carlone et al., 2016; van der Hoeven Kraft et al., 2011; Jolley et al., 2018). Despite these benefits, university support for field courses is diminishing, highlighting the importance of research that explores barriers, outcomes, and impacts of field courses (Cotton & Cotton, 2009; Moore, 2001; Smith, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear whether this rapid conversion resulted in net gains or losses to students. On one hand, it is difficult to imagine how the development of skills, self‐efficacy, and community would be possible without in‐person interactions (Beltran et al., 2020; Carlone et al., 2016; Epstein et al., 2015; Mason et al., 2018). On the other, traditional field courses still remain inaccessible to many students, especially URM, due to course fees, institutional barriers (Cid & Bowser, 2015; Morales et al., 2020), limited sense of belonging (O’Brien et al., 2020; Smith et al., 2014), and physical disabilities that may be mitigated in an online course.…”
Section: Introductionmentioning
confidence: 99%
“…These barriers result from overly narrow views of knowledge and practices that disrupt participation in STEM across kindergarten through grade 12 (K12) and collegiate education (Champion & Mesa, 2018;Kelly, 2009). Guidelines on the content of U.S. K12 STEM education have attempted to broaden beyond lists of topics to include discipline-based practices, e.g., Standards for Mathematical Practice (NGACBP & CCSO, 2010) and Science and Engineering Practices (NRC, 2013); however, these policies also amplify divisions between school science and math and the content of STEM used every day (Booker & Goldman, 2016;Carlone et al, 2016). These barriers between formal and informal STEM learning are echoed in many international educational settings (Morris et al, 2019;Yang et al, 2021).…”
Section: Systems Barriers To Participation In Stem Education and Stem...mentioning
confidence: 99%
“…International STEM informal education research has documented approaches that break barriers to diverse communities' STEM participation. Some promising practices have taken place in hybrid spaces outside of schools, such as camps, clubs, and programs associated with community-based organizations (Archer et al, 2021;Booker & Goldman, 2016;Carlone et al, 2016;National Research Council, 2015). Research on informal learning has suggested that when youth develop STEM interests and identities via hybrid spaces they are more likely to weather some of the persistent STEM barriers in schools and persist in their STEM interests (McCreedy & Dierking, 2013;Shaby et al, 2021).…”
Section: Systems Barriers To Participation In Stem Education and Stem...mentioning
confidence: 99%
“…Ecology is a dynamic discipline for making visible the development and refinement of disciplinary practices, with adaptation in the field necessitated by the complexity and messiness of transforming complex systems through tools and texts (Forsythe, 2018; Manz, 2015, 2016). Ecology is also a field of study engaged in navigating varying epistemological traditions of science teaching and learning, resisting depictions of science practice as purely cognitive and decontextualized towards more holistic and just relations with the world (Bang & Marin, 2015; Bang & Medin, 2010; Bang et al, 2013; Carlone, 2016; Haraway, 1991, 2016; Hecht & Nelson, 2021; Jaggar, 1989). Importantly, expansive conceptualizations of the discipline and disciplinary practices that center emotion and place are generating innovative insights into how complex ecological systems communicate and sustain themselves, in turn, disrupting narrowed depictions of how doing science should look, sound, and feel (Jabr, 2020; Kimmerer, 2013; Simard, 2021).…”
Section: Introductionmentioning
confidence: 99%